2022
DOI: 10.1177/20556683211072384
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality and well-being in older adults: Results from a pilot implementation of virtual reality in long-term care

Abstract: Introduction This paper describes the findings of a pilot implementation project that explored the potential of virtual reality (VR) technology in recreational programming to support the well-being of older adults in long-term care (LTC) homes. Methods 32 Adults in four LTC homes participated in a pilot implementation project where they viewed VR experiences of popular locations in Canada created especially for this project. Data in this paper are based on multiple viewing experiences ( n = 102) over a two-wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 34 publications
(74 reference statements)
0
11
0
Order By: Relevance
“…The residents also took time to become familiar with the equipment. Some residents felt giddy and dizzy ( Brimelow et al, 2022 ; Chaze et al, 2022 ) while others felt headache, a heavy head feeling or nervousness while trying VR in the beginning. The staff has to be prepared to help residents remove the headset and provide support for safety, as needed ( Chaze et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The residents also took time to become familiar with the equipment. Some residents felt giddy and dizzy ( Brimelow et al, 2022 ; Chaze et al, 2022 ) while others felt headache, a heavy head feeling or nervousness while trying VR in the beginning. The staff has to be prepared to help residents remove the headset and provide support for safety, as needed ( Chaze et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some residents felt giddy and dizzy ( Brimelow et al, 2022 ; Chaze et al, 2022 ) while others felt headache, a heavy head feeling or nervousness while trying VR in the beginning. The staff has to be prepared to help residents remove the headset and provide support for safety, as needed ( Chaze et al, 2022 ). Ferguson et al (2020) raised a practical and salient point about staff education; staff must be trained about the technology and be familiar with the residents’ preferences to tailor the program accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…All data collected using the Interact Short instrument, PAINAD instrument and qualitative interviews is reported elsewhere. 30 Here we present the Interact Short and PAINAD data by site location, to understand differences in efficacy between sites. The scores in Figure 1 represent the percentage of experiences at each site that scored a 4 or 5 (out of 5) for each aspect of the Interact Short questionnaire.…”
Section: Resultsmentioning
confidence: 99%
“…In another study on a two-week VR intervention participants of the experimental group using the VR system reported being less socially isolated, being less likely to show signs of depression, and feeling better about their overall well-being, compared to the TV viewing group [ 16 ]. Previous research on the benefits of VR intervention has demonstrated a positive impact on the social well-being of older adults, particularly its potential to increase social interaction and provide a sense of accomplishment and improve mood [ 17 ]. VR possesses the potential to increase engagement between older adults and those around them, by providing topics of conversation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on the benefits of VR intervention has demonstrated a positive impact on the social well-being of older adults, particularly its potential to increase social interaction and provide a sense of accomplishment and improve mood [ 17 ]. VR possesses the potential to increase engagement between older adults and those around them, by providing topics of conversation [ 17 ]. Another study revealed that a combination of 3D VR and hands-on aromatherapy significantly improved the happiness, perceived stress, sleep quality, meditation experience, and life satisfaction in institutionalized older adults [ 18 ].…”
Section: Introductionmentioning
confidence: 99%